RP-HPLC Method for Simultaneous Estimation of Azithromycin and Ambroxol Hydrochloride in Tablets - Venkatesh, V.; Elphine Prabahar, A.; Venkata Suresh, P.; Uma Maheswari, Ch.; Rama Rao, N. (Asian Journal of Chemistry, 2010)
An isocratic RP-HPLC method has been developed and validated for simultaneous analysis of azithromycin with ambroxol hydrochloride in combined solid dosage forms. It is simple, accurate, economical and reproducible for simultaneous estimation of two component drug mixture. Chromatography was performed on a 250 mm × 4.6 mm, 5 μm particle size, C18 (ODS) column with a methanol:acetonitrile:phosphate buffer in ratio of 50:20:30 pH 5.0 as mobile phase at the flow rate of 1 mL/min. The detection wavelength was 260 nm and analysis was performed at room temperature. Linearity was observed in concentration range of 25-125 μg/mL of azithromycin and 5-25 μg/mL of ambroxol hydrochloride. Different analytical parameters such as linearity, precision, accuracy and robustness were determined according to International Conference on Harmonization ICH Q2B guidelines. Results of analysis were validated statistically and by recovery studies.